A Novel Infrastructure 2 Pedestrian Approach to Increase Human Life and Health Safety - Pawel SKOKOWSKI; Krzysztof MAŚLANKA (Communications of International Proceedings, 2020)
This paper presents a novel Infrastructure 2 Pedestrian approach to increase human life and health safety. After introducing the reader to the subject of the issue, the authors motivate their research area to improve pedestrian safety on the roads. In addition to purely human arguments, the economic factors supporting the need to develop this type of solution are also presented. Then, the concept of the proposed method and selected use cases with the possibility of applying the solution are introduced. The authors also estimate the potential profits from the implementation of the proposed concept. The article summarizes brief conclusions.
Keywords: pedestrian safety; infrastructure to pedestrian (I2P); accidents; human life.